Factors associated to infant mortality in Sub-Saharan Africa - Pablo Viguera Ester; Alberto Torres; José M. Freire; Valentín Hernández; Ángel Gil (AOSIS, 2011)
Half of the 10 million children who die annually in the world are from Sub-Saharan Africa (SSA). The reasons are known, but lack of will and resources avoid the development of sustainable policies. Associated factors to the high infant mortality rate (IMR) in SSA have been investigated in this research. An ecological multi-group study was designed comparing rates within SSA. The dependent variable is the IMR and health services, economic and development indicators are the independent variables. Information and data sources were WHO, World Bank, UNICEF and UNDP (1997-2007). IMR mean value is 92.2 (per 1000 live births) and a relationship with several of the factors could be observed. In the bi-variate analysis direct relationship was observed with maternal mortality rate and an inverse relationship was observed with prenatal care coverage, births assisted by skilled health personnel, gross national income per capita, per capita government expenditure on health, social security expenditure, adult literacy rate, net primary school enrolment rate, population with access to safe drinking water (in urban and rural areas) and with population with access to basic sanitation in rural areas. In the multi-variate analysis IMR had an inverse relationship with children under 5 years with diarrhoea who receive oral re-hydration, with social security expenditure as percentage of general government expenditure on health and with per capita government expenditure on health. The situation in SSA would change if their inhabitants received education and information to demand more equitable polices and better investments from their governments.